IMPLEMENTASI KEBIJAKAN PEMBANGUNAN WADUK JATI GEDE TERHADAP MATA PENCAHARIAN MASYARAKAT DI KECAMATAN JATI GEDE KABUPATEN SUMEDANG - ABDULLOH ABDULLOH; ENGKUS ENGKUS; HELDI HELDI (Prodi Ilmu Administrasi Negara, Universitas Al Ghifari, 2020)
The implementation of Policy is the objectives achieve of the policies. But the problem that often seem to give detriment to the society. Likewise in the implementation of development policies of Jatigede reservoir that causes the loss and the changes of their livelihoods.This study aims to determine how much the dimension influence in which the contents of policy implementation i.e. the content of the policy and environmental policy on the livelihood of people in the Jatigede district in Sumedang regency.The theory used in this study for the variable X are the theory of Merilee S, and Grindle’s theory (1980) in AG.Subarsono 2011: 93-94 that is about the content of the policy and the policy environment while the variable Y uses the theory of Adon Nasrulloh Jamaludin (2015), namely agriculture and non-agriculture.The method used is quantitative method with associative approach.Collecting of data was conducted through literature study and field study( unstructured interviews, observations,and questionnaires distributed to 100 respondents) with proportionate stratified random sampling technique.Based on the result, it is shown that the contents of the policy affect the people's livelihood (34.7%) and the remaining (65.3%) is influenced by other variables, the policy environment affect the people's livelihood by 52.0% and the remaining 48.0% is influenced by variables more. As for the variable policy implementation a significant influence amounted to 46,5% and 53,5% influenced by other variables. It can be concluded that there is a high impact of the policy implementation to livelihoods.